Erratum: Disappearance of partonic collectivity in √ sNN = 3 GeV Au+Au collisions at RHIC (Physics Letters B, (2022), 827, 137003) - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN = 3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2025 The Authors.
Keywords: Baryonic interactions; Collectivity; High baryon density; NCQ scaling; STAR experiment; dept.phy